Pure Laparoscopic Left Hemihepatectomy for Hepatic Peribiliary Cysts with Biliary Intraepithelial Neoplasia - Akira Umemura; Takayuki Suto; Akira Sasaki; Hiroyuki Nitta; Seika Nakamura; Fumitaka Endo; Kazuho Harada; Kazuyuki Ishida (Case Reports in Surgery)
Introduction. Hepatic peribiliary cysts (HPCs) usually originate due to the cystic dilatation of the intrahepatic extramural peribiliary glands. We describe our rare experience of pure laparoscopic left hemihepatectomy (PLLH) in a patient with HPCs accompanied by a component of biliary intraepithelial neoplasia (BilIN). Case Presentation. A 65-year-old man was referred for further investigation of mild hepatic dysfunction. Contrast-enhanced computed tomography showed dilatation of the left-sided intrahepatic bile duct, and biliary cytology showed class III cells. The patient was highly suspected of having left side-dominated cholangiocarcinoma and underwent PLLH. Microscopic findings revealed multiple cystic dilatations of the extramural peribiliary glands; hence, this lesion was diagnosed as HPCs. The resected intrahepatic bile duct showed that the normal ductal lumen comprised low columnar epithelia; however, front formation on the BilIN was observed in some parts of the intrahepatic bile duct, indicating that the BilIN coexisted with HPCs. Conclusion. We chose surgical therapy for this patient owing to the presence of some features of biliary malignancy. We employed noble PLLH as a minimally invasive procedure for this patient.